Command line and Graphical interface comparative analysis for ARP Poisoning through Ettercap - Prudhviraj, S; Sudha, C (International Journal of Computer Sciences and Engineering, 2025)
There has been many changes taking place in the recent arena of Address Resolution Protocol (ARP) Poisoning from the command line interpretation to the graphical interfaces that are developed. The process of ARP Poisoning is one of the famous techniques amongst present Man in The Middle (MITM) attacks. It is applicable to access the various unsecured websites authentication details which can be captured by the attacker and can be visualized on both the command line and graphical user interface (GUI). The entire process or communication takes place through the ethernet or local area network (LAN) and the result of the poisoned address is the physical address of the LAN which acts as a common interface between both the attacker and victim’s machine. This paper, there by explains the entire mechanism of ARP Poisoning that takes place through the LAN by both the command line interpretation (CLI) and the GUI Ettercap which shows the differences amongst both the methods and determines the best method which has the least complexity